Presepsin: gelsolin ratio, as a promising marker of sepsis-related organ dysfunction: a prospective observational study - Ragán, Dániel; Kustán, Péter; Horváth-Szalai, Zoltán; Szirmay, Balázs; Miseta, Attila; Woth, Gábor; Kőszegi, Tamás; Mühl, Diána (Frontiers in Medicine, 2023)
Introduction: We aimed to facilitate the diagnosis and prognosis of sepsis-related organ dysfunction through analyzing presepsin (PSEP) and gelsolin (GSN) levels along with a novel marker, the presepsin:gelsolin (PSEP:GSN) ratio. Methods: Blood samples were collected from septic patients at the intensive care unit (ICU) at three time points (T1-3): T1: within 12h after admission; T2: second day morning; T3: third day morning. Sampling points for non-septic ICU patients were T1 and T3. PSEP was measured by a chemiluminescence-based POCT method while GSN was determined by an automated immune turbidimetric assay. Data were compared with routine lab and clinical parameters. Patients were categorized by the Sepsis-3 definitions. PSEP:GSN ratio was evaluated in major sepsis-related organ dysfunctions including hemodynamic instability, respiratory insufficiency and acute kidney injury (AKI). Results: In our single center prospective observational study, 126 patients were enrolled (23 control, 38 non-septic and 65 septic patients). In contrast to controls, significantly elevated (p<0.001) admission PSEP:GSN ratios were found in non-septic and septic patients. Regarding 10-day mortality prediction, PSEP:GSN ratios were lower (p<0.05) in survivors than in non-survivors. PSEP:GSN ratios were also higher (p<0.001) in patients with sepsis-related AKI than septic non-AKI patients during follow-up, especially in sepsis-related AKI patients needing renal replacement therapy. Furthermore, increasing PSEP:GSN ratios were in good agreement (p<0.001) with the dosage and the duration of vasopressor requirement in septic patients. Moreover, PSEP:GSN ratios were markedly greater (p<0.001) in patients with septic shock than in septic patients without shock. Compared to septic patients requiring oxygen supplementation, substantially elevated (p<0.001) PSEP:GSN ratios were observed in septic patients with demand for mechanical ventilation, while higher PSEP:GSN ratios (p<0.001) were also associated with extended periods of mechanical ventilation requirement in septic patients. Conclusions: PSEP:GSN ratio could be a useful complementary marker besides the routinely used SOFA score regarding the diagnosis and short term mortality prediction of sepsis. Furthermore, the significant increase of this biomarker may also indicate the need for prolonged vasopressor or mechanical ventilation requirement of septic patients. PSEP:GSN ratio could yield valuable information regarding the extent of inflammation and the simultaneous depletion of the patient’s scavenger capacity during sepsis.